Use of Songs, Rhymes and Games in Teaching English to Young Learners in Bangladesh - Ara, Shaheen (Dhaka University Journal of Linguistics, 2010)
Although children learn a language faster than adults, they do not learn through traditional language teaching methods. Through fun activities children can learn a language better as learning becomes natural for them since these activities do not make them conscious that they are learning a language. In Bangladesh, since a proper learning atmosphere has not been ensured in children's English classes according to children's interest and psychological characteristics, benefit is yet to come from the compulsory English education at the primary level. In order to appeal to young learners' learning styles, songs, rhymes and games can be very effective tools for teaching children a foreign language. These tools can be used in children's classes to utilize their natural ability to learn a language. This paper introduces the benefits of some interesting tools in teaching children English and also suggests incorporating them at the primary level English curriculum in Bangladesh. Keywords: young learners, second language, teaching techniques, songs, rhymes, games, primary education. DOI: 10.3329/dujl.v2i3.4150 The Dhaka University Journal of Linguistics: Vol.2 No.3 February, 2009 Page: 161-172